De bijdragen van Hongaarse studenten te Franeker in het Album Amicorum van Cornelis Burt Andriessen (1781–1782) - Postma, Ferenc (Acta Neerlandica, 2022)
In the summer of 2020, the Album Amicorum of the late Reverend Cornelis Burt Andriessen (1758–1845) came into the possession of the so-called “Academie van Franeker” Foundation. It is kept nowadays in the Library of the Foundation at Franeker. The Album contains six contributions written by Hungarian Peregrini during their stay at Franeker University, 1781–1782, where they met Andriessen as a student at the Faculty of Theology.